2019
DOI: 10.1002/nml.21370
|View full text |Cite
|
Sign up to set email alerts
|

The belonging model of trust

Abstract: Although we know that high‐quality employee–organization relationships are beneficial, these relationships are complex and not fully understood, especially among employees of nonprofit organizations. In particular, we know little about how these employees perceive trust, which may overlook an important contributor to effective management. We begin to address this issue by testing a new theoretical model that conceptualizes perceived insider status, psychological ownership, and organizational identification as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 89 publications
(134 reference statements)
0
9
0
Order By: Relevance
“…These intrinsic values and sense of belonging may be linked to trust in the organisation. Key aspects of belonging include psychological ownership and perceived insider status (Knapp et al, 2019). However, this intrinsic value can be eroded through factors, including job demands, workload, job insecurity, ageing workforce and changes in the job structure, leading to individual health problems and, in turn, creating pressure on the performance of organisations (Deloitte Access Economics, 2018; García-Herrero et al, 2013; Safe Work Australia, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These intrinsic values and sense of belonging may be linked to trust in the organisation. Key aspects of belonging include psychological ownership and perceived insider status (Knapp et al, 2019). However, this intrinsic value can be eroded through factors, including job demands, workload, job insecurity, ageing workforce and changes in the job structure, leading to individual health problems and, in turn, creating pressure on the performance of organisations (Deloitte Access Economics, 2018; García-Herrero et al, 2013; Safe Work Australia, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that trustworthy and transparent behavior will increase employee connectedness and perceived insider status (Colquitt and Rodell, 2011). Although some recent studies have found that perceived insider status as belongingness will increase employees' trust in the organization, they also did not clarify the reciprocal relationship between trust and perceived insider status (Knapp et al, 2019). research also suggests that managerial feedback to employees positively develops their perception of being insiders (Chen et al, 2017).…”
Section: Managerial Trustworthy Behavior and Perceived Insider Statusmentioning
confidence: 94%
“…Their responses are perhaps because nonprofit workers are the lifeblood enabling nonprofit organizations to deliver services that ultimately generate shareholder benefits. For instance, Knapp et al ( 2019 ) argued that nonprofit managers should receive training to apply organizational policies consistently and equitably. In addition, the organization should clearly explain the underlying rationale behind its decisions (i.e., layoffs).…”
Section: Discussionmentioning
confidence: 99%
“…However, the internal view—although no less important—has received considerably less attention than the external view. The internal perspective focuses on the dynamics of interpersonal trust within nonprofit organizations and has more recently garnered attention for its impact on overall organizational performance (Greiling, 2007 ; Knapp et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation